47‐3: High Efficiency and High PPI AMOLED with Cavity Tuned by Inkjet Printed Hole Injection Layer. Issue 1 (30th May 2018) - Lee, Meng-Ting; Lu, Kun-Ta; Chen, Yi-Hong; Lin, Kuan-Heng; Chen, Wen-Pin; Chen, Tsu-Wei; Chen, Kuo-Kuang; Lu, Hsueh-Hsing; Lin, Yu-Hsin; Walker, Daniel; Creally, Matthew; Béalle, Gaëlle; et al.
Abstract : A low‐cost AMOLED with 10µm sub‐pixel width is fabricated without using a FMM. Solution hole injection layers were printed on a TFT array panel to replace multiple thicknesses of ITO commonly used for cavity tuning, resulting in a new process with low cost and high pixel density. The panel using inkjet‐printed hole injection layer achieved the same performance as a panel using ITO only. The panel achieved a high NTSC ratio of 95.6% coverage and a reflectivity of ambient light lower than 6%, thanks to a precise alignment of AMOLED sub‐pixels and a RGB color filter rather than a circular polarizer.